Effects of Buchenavia tomentosa consumption on female rats and their offspring - doi: 10.4025/actascibiolsci.v32i4.7220 - Hugo Miranda Maciel Nunes; Joseilson Alves de Paiva; Adriano Tony Ramos; Paulo César Maiorka; Viviane Mayumi Maruo (Acta Scientiarum. Biological Sciences, 2010)
Buchenavia tomentosa Eichler is a common plant in Brazilian cerrado. Fruits of this plant are employed in human feeding and folk medicine. Cattle producers affirm that consumption of the fruits cause abortion in cows, and even death. Considering that the plant may be consumed by pregnant women and animals, the present study was undertaken to evaluate the possible toxic effects of the ingestion of B. tomentosa fruit (10% added to the diet), from the first to the twenty-first days of gestation, on reproductive parameters and on physical and neurobehavioral development of rats offspring. An increase in food consumption at pregnancy days 11 and 17, and weight increase at day 17 of pregnancy were observed. Besides that, we verified an increase in weight of male offspring on post natal day 1. Other parameters were not affected by plant consumption. These results indicate that the consumption of B. tomentosa at 10% during pregnancy cause slight toxicological effects. The changes verified in the present study indicate toxic action of the fruit possibly induced by flavonoids with hormonal action; however, further studies must be accomplished to corroborate this hypothesis.